Correlation between soluble urokinase plasminogen activator receptor with CD4 T lymphocyte and WHO clinical staging of HIV infection - Wardhani, Shinta Oktya; Burhan, Niniek; Ismanoe, Gatoet; Yudani, Tri (Institute of Topical Disease Universitas Airlangga, 2010)
The urokinase-type plasminogen activator (uPA) and its receptor play a key role in pericellular proteolysis, cell migration and signal transduction. Previous study showed that suPAR could be used as an independent prognostic marker of disease progression in HIV-1 patients.1,17 Immune status of HIV patient and progressivity of disease are important parameters used as clinical concideration before initiating anti retroviral treatment and for monitoring treatment effectivity. Recently immune status of HIV patients is determined by CD4 T lymphocyte counting which represents the remaining healthy lymphocyte T expressing CD4 that very expensive and need special laboratory equipment. Destruction and shedding of T lymphocyte, macrophage and natural killer cell will deliver soluble urokinase plasminogen activator receptor, a surface protein which is expressed by those cells and can be measured by ELISA8,9,11. This study objective is to determine correlation between suPAR plasma concentration and CD4 T lymphocyte and WHO clinical stagging of HIV infection. Study subjects. Fifty four naieve HIV-1-infected patients (32 males, and 22 females) are participant in a cross sectional study enrolled on 22 November 2007 until 31 july 2008 at the department of infectious disease Saiful Anwar Hospital, Malang, Indonesia. Blood sampling. Two blood samples were drawn before treatment, CD4 counts were measured with an Epics XL-MCL Coulter flowcytometer. EDTA plasma for suPAR measurement was stored at -80°C. Data are presented as mean±standart deviation. P<0.05 is considered significant. Statistical calculations were done using SSPS 15. Patients (n = 54) enrolled and clustered according to WHO clinical stage ( I - IV) at inclusion. All HIV-infected patients had measurable levels of plasma suPAR with a median value of 8,9 ng/mL(range 1,65-29,7 ng/mL). Pearson correlation demonstrated a weak but significant negative between suPAR and CD4 T lymphocyte count (p=-0.634, p<.0005). suPAR level positively correlated with the WHO-defined clinical stages (P< .0005, spearman correlation test, r=0,87). There were significant difference between each stage i.e I(1,6± o,61ng/mL), II(3.04±1.03 ng/mL), III (10.53±7.1ng/mL) and IV (20.42±10.81ng/mL) (P< .0005, Spearman test). In addition pearson correlation demonstrated a weak but significant negative correlation between suPAR and CD4 count (p=-0.66; P<.0005). There were negative significant correlatio between CD4 count and suPAR level, suggested that suPAR could provide as a complementary biological marker for HIV-1 although it can not replace the CD4 count. SuPAR plasma concentration and clinical stage give significantly correlation with WHO clinical staging of HIV infection.